Hypervelocity Impact Phenomenon in Bulk Metallic Glasses and Composites**. Issue 1 (24th September 2013) - Hamill, Lee; Roberts, Scott; Davidson, Marc; Johnson, William L.; Nutt, Steven; Hofmann, Douglas C.
<x xml:space="preserve">Abstract</x> Collisions with debris are major cause of concern for spacecraft and satellites. Developing new materials that can combat these threats, while still providing low‐density and sufficient toughness to survive launch loads, is important for future spacecraft design. In the current work, hypervelocity impacts are used to estimate the ballistic limit for bulk metallic glass and their composites and to investigate spalling behavior. The composites are shown to have excellent combinations of hardness and toughness for use as shields.